Paved With Good Intentions: Hospital Visitation Restrictions in the Age of Coronavirus Disease 2019*. Issue 10 (October 2020) - Andrist, Erica; Clarke, Rachel G.; Harding, Meghan
Abstract : Hospital visitation restrictions have been widely implemented during the coronavirus disease 2019 pandemic as a means of decreasing the transmission of coronavirus. While decreasing transmission is an important goal, it is not the only goal that quality healthcare must aim to achieve. Severely restricted visitation policies undermine our ability to provide humane, family-centered care, particularly during critical illness and at the end of life. The enforcement of these policies consequently increases the risk of moral distress and injury for providers. Using our experience in a PICU, we survey the shortcomings of current visitation restrictions. We argue that hospital visitation restrictions can be implemented in ways that are nonmaleficent, but this requires unwavering acknowledgment of the value of social and familial support during illness and death. We advocate that visitation restriction policies be implemented by independent, medically knowledgeable decision-making bodies, with the informed participation of patients and their families.